PERANCANGAN SISTEM PEMBANGKIT LISTRIK TENAGA HYBRID PADA POMPA AIR UNTUK TANAMAN HIDROPONIK - Lilik Ade Putri; Muhammad Hafiz; Nofriyani Nofriyani; Zanu Saputra (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2021)
Technological developments in the agricultural sector can use the DFT hydroponic system. But this hydroponic system uses a lot of electrical energy, this is due to the use of a pump for 24 hours. One way to increase electrical energy efficiency is to combine two energy sources, namely PLN and PLTS, which is called a hybrid system. The purpose of this tool is to obtain the results of an efficiency comparison analysis between PLN and PLTS (hybrid) by displaying the power usage and costs of the system. In this tool, what is done is to make a control system, monitor battery charging and battery discharge by voltage sensors and current sensors controlled by Arduino ATmega 2560 and monitoring power usage on AC pumps by Pzem sensors. In this study the hybrid system from PLTS will switch to PLN automatically when the battery is under 11.7 V voltage and will change to from PLN to PLTS when the battery voltage has reached 13 V. The results of the data from this hybrid system obtained a power efficiency of 42.96% PLN usage per day (24 hours). From the comparison of the PLN system with a hybrid system that uses an AC pump, a cost efficiency savings of IDR 213.6 rupiah is obtained for one day use. Keywords: Sensor, Battery, AC Pump, Solar Panel, Arduino Atmega 2560